Ultrasound-guided percutaneous removal of soft-tissue foreign bodies in children - Pradyumna Pan (Wolters Kluwer Medknow Publications, 2021)
The aim of the study was to determine the effectiveness and complications of ultrasound (US)-guided percutaneous removal of foreign bodies (FBs). Eleven patients were evaluated for US-guided percutaneous removal of FBs in the upper and lower extremities between April 2018 and March 2020 at the pediatric surgery department of a tertiary-level referral hospital. Elongated FBs, without damage to the adjacent neural and vascular tissue, were included. FBs with open wound, those with glass piece, and irregular-shaped and very superficial palpable FBs were excluded.